2015
DOI: 10.1177/0974930615609482
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional Roads

Abstract: Rural roads are built to improve people's mobility and to enhance access to markets, administrative centres, schools and health posts, and are credited with important socio-economic changes. A less studied aspect is the impact of roads on hydrological resources, as roads interact with existing surface and groundwater flows, redistributing water-related hazards and resources across space with significant consequences on people and their livelihoods. In Ethiopia, the government has embarked on a massive road con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 18 publications
1
4
0
Order By: Relevance
“…In this study, years of schooling is found to positively influence the adoption of RWH technology. Our results show that as years of schooling increase by one year, the probability of RWHP use increases by 17%; this is similar to the findings of [24,36]. This is because education increases access to information about innovation, inputs and their uses, and the management of technology, all of which are crucial to creating positive attitudes towards technology adoption.…”
Section: Descriptive Resultssupporting
confidence: 81%
See 3 more Smart Citations
“…In this study, years of schooling is found to positively influence the adoption of RWH technology. Our results show that as years of schooling increase by one year, the probability of RWHP use increases by 17%; this is similar to the findings of [24,36]. This is because education increases access to information about innovation, inputs and their uses, and the management of technology, all of which are crucial to creating positive attitudes towards technology adoption.…”
Section: Descriptive Resultssupporting
confidence: 81%
“…Better market connections reduce the transaction costs caused by information asymmetry and increase the availability and uses of the support services that can promote technology adoption [34]. An empirical study in Ethiopia found that access to markets and a shorter distance from rural towns affects the purchase of inputs by rural households [19,24]. The negative relationship indicates that households living far from roads are less likely to use road water harvesting practices; as such, plots get less attention from these households and are less accessible via the small structures constructed through road water harvesting projects.…”
Section: Descriptive Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The negative aspects of rainfall can be reversed if roads are systematically used as instruments for rainwater harvesting [Nissen-Petersen 2006]. Thus, road harvesting can generate substantial positive impacts: more secure water supply, better soil moisture, reduced erosion and respite from harmful damage [Demenge et al 2015].…”
Section: Introductionmentioning
confidence: 99%